Effectiveness of Capital Regulation at U.S. Commercial Banks, 1985 to 1994 - Hovakimian, Armen; Kane, Edward J. (Journal of Finance, 2000)
Unless priced and administered appropriately, a governmental safety net enhances risk‐shifting opportunities for banks. This paper quantifies regulatory efforts to use capital requirements to control risk‐shifting by U.S. banks during 1985 to 1994 and investigates how much risk‐based capital requirements and other deposit‐insurance reforms improved this control. We find that capital discipline did not prevent large banks from shifting risk onto the safety net. Banks with low capital and debt‐to‐deposits ratios overcame outside discipline better than other banks. Mandates introduced by 1991 legislation have improved but did not establish full regulatory control over bank risk‐shifting incentives.